PENGELOLAAN PRIVASI PADA PEKERJA KREATIF PENGGUNA MEDIA SOSIAL INSTAGRAM - Kevin Surya Laksmana, Muhammad; Naryoso, Agus; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The rapid development of digital technology and social media has led to the emergence of various new job opportunities, shifting job trends towards the use of digital media. For video creators, animators, photographers, graphic designers, or influencers, the presence of the Instagram social media platform can be utilized to shape a self-representation that supports their work, while also serving as a space to freely express themselves. Within this perceived safe space, Instagram users sometimes share highly personal and sensitive information on social media. Therefore, awareness and knowledge of social media behavior are needed to minimize the risks that may arise from the freedom of expression and self-disclosure in the online world. This research aims to understand how creative workers manage privacy through the Instagram social media platform. The study employs qualitative research methods, an interpretive paradigm, phenomenological approach, and in-depth interview data collection techniques. In analyzing the unique experiences of the informants, the Communication Privacy Management theory and the concept of self-presentation in Dramaturgy Theory are utilized.The results of this research reveal how creative workers who are Instagram users strive to manage their privacy to shape an ideal self-image to support their work. In operating Instagram while considering information boundaries, creative workers engage in a series of stages ranging from observation, planning, categorizing information, implementing strategies, to monitoring their posts. This study also highlights that there are several criteria considered by creative workers to set their privacy boundaries in the effort of self-disclosure. Each individual has specific motives for uploading information, considering cultural aspects, social context, gender values, and weighing the risks and benefits as consequences of self-disclosure. Additionally, the ideal self-presentation on Instagram is also manifested by creative workers using strategies such as self-promotion and ingratiation.